Más allá del postpunk. New romantics y góticos entre Madrid y Valencia en los años ochenta - Eduardo Leste; Fernán del Val (Resonancias, 2019)
This article restores, through in-depth interviews, the memory of the youth who participated in diverse musical scenes and youth cultures that emerged in Madrid and Valencia in the eighties. From the stories of those people, and the use of the concepts of music scene and youth culture, this article delves into the connections between the Movida madrileña –mainly of the gothic and new romantics cultures– the Valencian postpunk scene and the incipient Valencian Bacalao, showing the relations of competition and emulation among them, that will end up generating the so-called Bacalao madrileño in the nineties. In this way, this work, along with adding in complexity to the phenomenon of the Movida madrileña, makes visible those young people who participated with their own speeches and practices, often anonymously, of those cultural productions.